การประเมินภาวะสุขภาพจากการรับสัมผัสโลหะเหล็กของผู้ประกอบอาชีพทำมีด - พรเจริญ อัจฉราวลัย; บดีรัฐ นริสา เก่งตรง; ฤกษ์งาม ถวัลย์; ชูเมียน สิรินารถ (Thai Journal of Science and Technology, 2019)
Abstract Welder is the traditional occupation in Thailand. It is the most common work for knife making in Tha Chang, Nakhon-luang district in Ayutthaya. Iron fumes are undesirable products of the majority of welding operations and may have various detrimental effects on health. The purpose of this study was to measure the level of serum iron that affected to long-term occupational welding in order to investigate adverse health effect. Level of serum iron increased with the duration of exposure. The results showed significantly different of serum iron between welders and non-welders. In addition, there is no serious adverse health effect in welders exposed to iron fume. In conclusion, the occupational welders exposed to iron may increase the level of serum ferritin. Keywords: iron; serum ferritin; welder